2021
DOI: 10.3390/min11090991
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Source Rock Heating and Structural Changes in the Electromagnetic Fields Using Experimental and Mathematical Modeling

Abstract: The paper presents the results of an experimental study of heating and the structural resultant changes of source rocks under the influence of the electromagnetic field in the microwave and radio-frequency ranges. The samples from the Bazhenov Formation (West Siberia, Russia) and the Domanic Formation (Ural, Russia) have been tested. It is shown that samples from these formations demonstrate very different heating rates at the same electromagnetic field parameters and the their heating rate depends on the type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Hence, the study concluded that magnetic catalysts could be added in the thermal treatment of source rocks. Similar studies were conducted by Kovaleva et al [46] on source rock samples from the Bazhenov and Domanik formations. The study highlighted the difference in heating rates based on the electromagnetic field type.…”
Section: Advances In Experimental Studies Of Isc On West Siberian Sha...supporting
confidence: 78%
“…Hence, the study concluded that magnetic catalysts could be added in the thermal treatment of source rocks. Similar studies were conducted by Kovaleva et al [46] on source rock samples from the Bazhenov and Domanik formations. The study highlighted the difference in heating rates based on the electromagnetic field type.…”
Section: Advances In Experimental Studies Of Isc On West Siberian Sha...supporting
confidence: 78%
“…In the pursuit of enhancing microwave-assisted mineral processing, there is a pivotal need for concerted research efforts aimed at the development of holistic modeling frameworks. These comprehensive models are anticipated to deliver precise predictions of mineral responses within microwave fields, thereby facilitating the implementation of highly refined processing optimizations that are meticulously tailored to the distinct characteristics of specific ores [63,64]. Such an initiative necessitates the integration of the latest advancements in modeling and simulation technologies, setting the stage for the creation of microwave-treatment processes that are not only more effective but also markedly more energy-efficient.…”
Section: Process Optimization and Modelingmentioning
confidence: 99%
“…The influence of thermal treatment on the Domanik Formation was studied by Gafurova et al [23,24], Kovaleva et al [25], and Nasyrova et al [26]. The authors found that a change in the pore space and an increase in porosity occurs when the samples are heated, as a result of the transformation of organic matter and fracturing of the rock.…”
Section: Introductionmentioning
confidence: 99%